Effects of nanobubble water on the growth of Lactobacillus acidophilus 1028 and its lactic acid production. Issue 53 (30th September 2019) - Guo, Zitao; Wang, Xuezhi; Wang, Hanxiao; Hu, Bo; Lei, Zhongfang; Kobayashi, Motoyoshi; Adachi, Yasuhisa; Shimizu, Kazuya; Zhang, Zhenya
Abstract : Nanobubbles (NBs) in the culture medium may offer a new way of accelerating bacterial growth in the lag and logarithmic phases. Abstract : Nanobubble water (NBW) has been applied in various fields due to the unique properties of nanobubbles (NBs) including long-term stability, negative zeta potential and generation of free radicals. In this study, the performance of four kinds of NBW from different gases (air, N2, H2, and CO2 ) in addition to deionized water (DW) were investigated and compared in terms of the growth of the probiotic Lactobacillus acidophilus 1028. The NB density, size distribution, zeta potential, pH and dissolved oxygen (DO) of the NBW were firstly investigated. Results indicate that N2 -NBW had the highest absolute value of zeta potential and NB density (−25.3 ± 5.43 mV and 5.73 ± 1.0 × 10 7 particles per mL, respectively), while the lowest was detected in CO2 -NBW (−6.96 ± 2.36 mV and 3.39 ± 1.73 × 10 7 particles per mL, respectively). With the exception of CO2 -NBW, all the other types of NBW showed promotion effects on the growth of the strain at the lag and logarithmic phases. Among them, N2 -NBW demonstrated the best performance, achieving the highest increase ratio of 51.1% after 6 h cultivation. The kinetic models (Logistic and Gompertz) indicate that the culture with N2 -NBW had the shortest lag phase and the maximum specific growth rate when compared to the H2 -NBW and DW groups under the same cultivation conditions. Preliminary analysis on the mechanisms suggested that these effects were related to the properties (zeta potential and density) of the NBs, which might affect the transport of substances. This study suggests that NBW has the potential for promoting the production efficiency of probiotics via fermentation.